PENGARUH LOYALITAS, PRESTASI KERJA, DAN SENIORITAS TERHADAP PROMOSI JABATAN PADA PT PACTO LTD DI BALI - Hariyanti, Azyyati Umi; Giantari, I Gusti Ayu Ketut (E-Jurnal Manajemen, 2019)
Loyalty, work performance and seniority have known to have an impact on promotion. This study intends to identify these correlations in 77 employees at PT. PACTO Ltd in BALI through saturated sampling techniques and data collection s with interview s and questionnaire s . Multiple linear regression analysis is a technique use in research and found loyalty, work performance, and seniority positively correlated with job promotion. Employees are expected to have good cooperation with other employees and continue to improve their abilities so that all tasks from the company can be done as well as possible. The management should better consider the employee's tenure, so that all senior employees have equal opportunities to be promoted to higher positions. Keywords : loyalty,  job performance, seniority,  job promotion